Global trends and hotspots in research for sudden hearing loss over the past two decades: a bibliometric and visualization analyses - Di, Xueshi; He, Tiantian; Zhou, Yuqi; Li, Xiaonan; Feng, Juanjuan; Su, Chenyang; Bai, Peng (Frontiers in Neurology, 2025)
ObjectiveThis study aims to examine and visually map the characteristics, research hotspots, and emerging trends in sudden hearing loss research over the past two decades.MethodsA systematic search was conducted for English-language articles and reviews on sudden hearing loss published between 2004 and 2023 in the Web of Science Core Collection. Using Citespace, VOSviewer, and Bibliometrix, we performed a comprehensive analysis and visualization of publications, countries, institutions, authors, journals, and keywords.ResultsThe analysis identified 2,513 publications, 565 journals, 3,341 keywords, and 8,818 authors. The annual publication output has slightly increased. China has been the leading contributor to sudden hearing loss research, with strong collaborative ties to the United States. Hallym University ranks at the top among institutions. The journal Otology & Neurotology has the highest publication volume, while Laryngoscope is the most frequently co-cited journal. Key terms such as “deafness,” “sensorineural hearing loss,” and “therapy” dominate the keyword landscape. The pathogenesis and treatment of SHL are at the core of this research field, while “recovery,” “management,” and “prognostic factors” are gradually receiving broader attention.ConclusionThis study compiles and analyzes studies related to sudden hearing loss over the past 20 years, and presents bibliometric-based visual data on the progress and hotspots of sudden hearing loss research to provide researchers with references to help guide future sudden hearing loss research.